1999
DOI: 10.1200/jco.1999.17.5.1339
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of Fluorouracil Plus Cisplatin Versus Hydroxyurea as an Adjunct to Radiation Therapy in Stage IIB-IVA Carcinoma of the Cervix With Negative Para-Aortic Lymph Nodes: A Gynecologic Oncology Group and Southwest Oncology Group Study

Abstract: This study demonstrates that for patients with locally advanced carcinoma of the cervix, the combination of 5-FU and CF with RT offers patients better PFS and overall survival than HU, and with manageable toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
699
11
36

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,374 publications
(784 citation statements)
references
References 56 publications
16
699
11
36
Order By: Relevance
“…In recent years, several groups have reported concurrent chemoradiation to improve the survival of patients with locally advanced cervical carcinoma (Keys et al, 1999;Morris et al, 1999;Rose et al, 1999;Whitney et al, 1999;Peters et al, 2000). Cisplatin is the most active cytotoxic agent against cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several groups have reported concurrent chemoradiation to improve the survival of patients with locally advanced cervical carcinoma (Keys et al, 1999;Morris et al, 1999;Rose et al, 1999;Whitney et al, 1999;Peters et al, 2000). Cisplatin is the most active cytotoxic agent against cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, substantial advances in the management of locally advanced cervical cancer have been reported. Five randomised trials showed improved survival and local control when cisplatin-based chemotherapy was added concurrently to radiation treatment in patients with locally advanced cervical cancer (Keys et al, 1999;Morris et al, 1999;Rose et al, 1999;Whitney et al, 1999;Peters et al, 2000). This combined modality approach produced an absolute increase in 5-year survival of 12% as compared with radiation therapy alone and resulted in a sudden change in the standard of care for this disease.…”
mentioning
confidence: 99%
“…In 1999, the National Cancer Institute recommended CCRT as the standard approach for locally advanced cervical cancer, based on a 30-50% decrease in mortality (7)(8)(9)(10). In Europe, Japan and Latin countries, NAC followed by surgery (NCS) has emerged as a valid alternative and several pilot studies have shown a large benefit over RT alone in terms of overall survival (OS) and disease-free survival (DFS) (11).…”
Section: Introductionmentioning
confidence: 99%
“…A new standard for the treatment of locally advanced cervical cancer was established in 1999 [4,5]. The addition of weekly cisplatin at 40 mg/m 2 for 6 weeks in combination with radiation (RT) reduces the relative risk of death from cervical cancer by approximately 50% by decreasing local failure and distant metastases [6][7][8][9][10]. This combination was favored because Gynecologic Oncology Group (GOG) Protocol 120 showed it to be less toxic and as equally efficacious when compared with other combinations using hydroxyurea and/or 5-flourouracil (5-FU) [8].…”
Section: Introductionmentioning
confidence: 99%